Dilemmas in considering β-thalassemia status in subjects with borderline HbA2 values: a pilot study in Eastern India - Tridip Chatterjee; Amit Chakravarty; Sudipa Chakravarty (Thalassemia Reports, 2014)
Interpreting hemoglobin disorders by high performance liquid chromatography can sometimes deceptive, especially with borderline HbA2 values. It is often problematic, especially in antenatal cases if the partner is a known thalassemia trait. We tested for underlying β-thalassemia mutations in 24 subjects with borderline HbA2 values (between 3.0%-4.0%). Amplification refractory mutation system-polymerase chain reaction was used to detect the five common Indian β-thalassemia mutations: [IVS-I-5 (G>C), Cod 15 (G-A), Cod 8/9 (+G), Fr. 41/42 (-TTCT) and Cod 26 (G-A)]. β-globin gene sequencing was performed if no mutation was detected. β-globin gene defect was not identified in any of the samples. There was no presence of any of the five common mutations in the small cohort. The average value of HbA2 in 24 normal samples was found to be 3.96. The average values for mean cell volume and mean cell hemoglobin (MCH) were found to be 82 and 28.8 pg respectively. Among these 24 normal samples, 13 had MCH below 27 pg and 11 had MCH above 27 pg. On the contrary, one thalassemic family was screened, in which the father of an HbE-β thalassemia patient was found to have HbA2 3.1, being a β-thalassemia carrier. Mutation analysis should be offered to all at-risk couples with borderline HbA2, especially those with values between 3.5% and 4.0% and microcytic hypochromic indices. As, cases with some specific mutational background or clinical condition shows abnormally low HbA2, so mutation screening should be performed in other partner if one partner found to be carrier or patient of thalassemia.